Analysis of Charge Accumulation within Insulating Materials via Numerical Simulation - Laing M.; Nik Ali N.H.; Mohd Ariffin A.; Zaini N.H.; Yusoh M.A.T.M.; Fadzilah A.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric fields; Electric insulation; HVDC power transmission; Insulating materials; Numerical models; Permittivity; Polyethylenes; Temperature; Bulk power transmissions; Charge accumulation; Direct current transmissions; Direct-current; Economic efficiency; Electrical power; High-Voltage Direct Current; Power transmission systems; Reliability efficiencies; System reliability; Electric space charge